Intense Laser Pulse Interaction With Graphene and Graphene Ribbons - Faisal, F. H. M. (Frontiers in Chemistry, 2022)
A quantum mechanical analysis of interaction of intense ultrashort laser pulses with graphene monolayer and armchair graphene ribbons of different widths is made. To this end a TB Hamiltonian model of graphene and graphene ribbons is used. The Hamiltonian in the adiabatic representation is coupled to the laser field by the minimal coupling prescription in the reciprocal lattice space. The time-dependent wavefunction of the interacting system is obtained by solving the dynamical coupled equations for the occupation amplitudes of the valence and the conduction bands. They are solved numerically "exactly" to determine the transfer of population to an initially empty conduction band and generation of ultrashort pulses of charge-currents (electron-hole currents) in graphene as well as in "armchair" ribbons. The current pulses are analysed in terms of the intra-band electron-hole currents and, the inter-band polarisation currents. Also, an example of the radiation emitted from the current in graphene is briefly discussed. Both the transfer of population and the ultrashort charge-currents in graphene are found to produce a steady charge transfer a steady current in graphene that can persist after the laser pulse. The radiation spectrum emitted is found to be essentially continuous and is characterised by a broad plateau that extends to many (over a hundred) orders of incident photon energy. The possibility of controlling the characteristics of the ultrashort current pulse by choosing the laser pulse in also illustrated. It is found that the duration of the charge-current pulse could be made as short as the duration of the incident ultrashort laser pulse. Moreover, the phase of the charge-current pulse could be controlled by the carrier-envelope-phase (CEP) of the laser pulse. An example of this in an armchair ribbon is given. It shows that the phase of the current can be reversed by changing the CEP of the incident laser pulse from 0 to π.